East Asian Monsoon History and Paleoceanography of the Japan Sea Over the Last 460, 000 Years. Issue 7 (4th July 2018) - Gallagher, Stephen J.; Sagawa, Takuya; Henderson, Andrew C. G.; Saavedra‐Pellitero, Mariem; De Vleeschouwer, David; Black, Heather; Itaki, Takuya; Toucanne, Sam; Bassetti, Maria‐Angela; Clemens, Steve; Anderson, William; Alvarez‐Zarikian, Carlos; et al.
Abstract: The Japan Sea is directly influenced by the Asian monsoon, a system that transports moisture and heat across southeast Asia during the boreal summer, and is a major driver of the Earth's ocean‐atmospheric circulation. Foraminiferal and facies analyses of a 460‐kyr record from Integrated Ocean Drilling Program Expedition 346 Site U1427 in the Japan Sea reveal a record of nutrient flux and oxygenation that varied due to sea level and East Asian monsoon intensity. The East Asian summer monsoon (EASM) was most intense during marine isotope stage (MIS) 5e, MIS 7e, MIS 9e, and MIS 11c when the Tsushima Warm Current flowed into an unrestricted well‐mixed normal salinity Japan Sea, whereas East Asian winter monsoon (EAWM) conditions dominated MIS 2, MIS 4, MIS 6, and MIS 8 when sea level minima restricted the Japan Sea resulting in low‐salinity and oxygen conditions in the absence of Tsushima flow. Reduced oxygen stratified, low‐salinity, and higher productivity oceanic conditions characterize Terminations TV, TIII, TII, and TI when East China Sea coastal waters breached the Tsushima Strait. Chinese loess, cave, and Lake Biwa (Japan) and U1427 proxy records suggest EASM intensification during low to high insolation transitions, whereas the strongest EAWM prevailed during lowest insolation periods or high to low insolation transitions. Ice sheet/CO2 forcing leads to the strongest EAWM events in glacials and enhanced EASM in interglacials. Mismatches between proxy patterns suggest that latitudinal and land/sea thermal contrasts played a role in East Asian monsoon variability, suggesting that a complex interplay between ice sheet dynamics, insolation, and thermal gradients controls monsoonal intensity. Key Points: East Asian summer monsoon intensified in MIS 5, MIS 7, MIS 9, and MIS 11 when the Tsushima Current flowed into an unrestricted normal marine Japan Sea East Asian winter monsoon dominated MIS 2, MIS 4, MIS 6, and MIS 8 when sea level lows restricted the Japan Sea causing low‐salinity and oxygen conditions Reduced oxygen stratified, low‐salinity, and higher productivity oceanic conditions characterize Terminations TV, TIII, TII, and TI